2018
DOI: 10.1159/000492876
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combination of Anti-CTLA-4 and Anti-PD-1 on Gastric Cancer Cells Proliferation, Apoptosis and Metastasis

Abstract: Background/Aims: Gastric cancer (GC) is one of the most common and lethal varieties of cancers. Anticancer activities of anti-CTLA-4 and anti-PD-1 antibodies have been explored in different cancers, including GC. The study aimed to explore the role of combination therapy with anti-CTLA-4 and anti-PD-1 antibodies in GC cells, and understand the possible underlying molecular mechanism. Methods: MKN-45 and MGC-803 cells were divided into four groups, namely control, CTLA-4, PD-1, and CTLA-4&PD-1. Cell viability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…PD-1 has been used to treat advanced cancer patients in recent years and had certain therapeutic effects (1)(2)(3). In normal lung and cancer tissues, we found that there was a correlation between the factors of the constructed risk model and the expression level of PD-1.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…PD-1 has been used to treat advanced cancer patients in recent years and had certain therapeutic effects (1)(2)(3). In normal lung and cancer tissues, we found that there was a correlation between the factors of the constructed risk model and the expression level of PD-1.…”
Section: Discussionmentioning
confidence: 71%
“…Mechanism studies have shown that the anti-CTLA-4 and anti-PD-1 combined therapy could inhibit the activation of β-catenin, MAPK, and PI3K/AKT signaling pathways. Interference with PD-1 expression inhibited GC cell proliferation, migration, invasion, and EMT and induced cell apoptosis (2). Inhibition of BET protein expression inhibited the expression level of PD-1/PD-L1 in triplenegative breast cancer.…”
Section: Introductionmentioning
confidence: 94%
“…It was also reported that over-expression of CTLA-4 promotes the activation of the ERK1/2/MAPK pathway in different tumor types ( 67 , 68 ) and stimulated T-cells ( 69 ). Additionally, coordinated anti-CTLA-4 and anti-PD-1 treatment suppressed the protein levels of phosphorylated ERK1/2 ( 70 ). Our results demonstrate that CD80 treatment induces the phosphorylation of ERK1/2 in HCC1937 cells at short post-treatment times.…”
Section: Discussionmentioning
confidence: 99%
“…These neutralizing antibodies considerably not only suppressed metastasis and epithelial–mesenchymal transition (EMT) in MGC-803 and MKN-45 cells but also increased the levels of apoptosis. Therefore, combination therapy using CTLA-4 and PD-1-blocking antibodies may improve favorable outcomes in GC patients [ 174 ]. Another study was conducted by Ralph et al regarding inhibition of CTLA-4 using tremelimumab as a monoclonal antibody in esophageal adenocarcinoma and metastatic GC patients.…”
Section: Treatment Of Gastric Cancer Base On B7 Family Inhibitionmentioning
confidence: 99%